Land Cover Change Using Multi-Time Landsat Imagery with Geographic Information Techniques (Sig) in Iuphhk-Ha Forest Area, Buru Regency, Maluku Province - Hendrik Aponno; Stany Rachel Siahainenia (Syntax Idea)
Development of land cover change in IUPHHK-HA PT. Gema Hutani Lestari is very important to know, so that future patterns of land cover change can be predicted so that negative land cover changes can be prevented or reduced, so that land cover changes that occur can be analyzed. This study aims to access land cover change in the IUPHHK-HA PT. Gema Hutani Lestari between 2013, 2016 and 2018. The methodology used by this study is guided classification with maximum and visual likelihood estimates, spatial data analysis, field checks and using overlays for landsat 8 data in 2013, 2016 and 2018. This study shows that land cover in IUPHHK-HA in Buru Regency, Maluku Province in 2013-2016 changed from forest to open land (69.26%) and from forest to allang-allang (29.03%) dominated by Main Swamp Forest (39.27%), Primary Dry Forest 27.08% and Secondary Swamp Forest ± 17.12%. While the smallest land cover is 0.01% pasture. The largest land cover change occurred in the Secondary Dryland Forest which was reduced ± 693,444 Ha. The most significant change when compared to the situation in 2005 was the Bush Intervention Dryland Agriculture which increased ± 190.69%. Deforestation that occurred was ± 1,122.21 ha (± 160.32 ha / year) and degradation was ± 100.19 ha (± 14.31 ha / year).